Identification of area changes threshold between document of title and cadastral network database in least square environment / Wan Nur Fatihah Wan Omar - Wan Omar, Wan Nur Fatihah (2021)
The Department of Survey and Mapping Malaysia (JUPEM) and Land Offices are two important organizations for managing and maintaining the land administration system and also responsible for cadastral survey and ownership rights in Peninsular Malaysia. Both organizations have their own information systems called eCadastre in JUPEM and eLand in Land Offices. Nonetheless, the eCadastre and eLand systems work differently. This research was carried out to suggest a good tolerance of difference in area between documented value in document of title and NDCDB. In addition, the objectives are to compile selected data of certified plan from Land Registry Office and NDCDB in Mukim Arau, to analyse the difference in area between certified plan from Land Registry Office and JUPEM’s NDCDB and lastly to propose a good tolerance from the analysis of optimum difference area. A total of 100 certified plans will be overlay with NDCDB to found out the difference in area using MapInfo software. Based on the optimum difference area, a good and acceptable tolerance between certified plan and NDCDB will be proposed.